General Introduction to the Works of Saint Bernard (I) - Leclercq, Jean (Cistercian studies quarterly, 2005)
This article presents information related to the works of Saint Bernard. With regard to history, this is not the place to recount the life of Saint Bernard. Nevertheless, since his writings were intimately linked to the circumstances that marked his existence, it will be necessary to situate his writings in his life by recalling their chronology. His writings, and in particular those texts that have an autobiographical character, as is the case especially with the letters and prologues placed at the beginning of his treatises.